Effectiveness of a protein-supplemented very-low-calorie diet program for weight loss: a randomized controlled trial in South Korea - Cho, Eunbyul; Kim, Sohye; Kim, Hwa Jung; Cho, Belong; Park, Jin Ho; Kwon, Hyuktae; Kim, Ju Young; Go, Yumi; Kang, Dong Gyun; Shin, Eunyoung; Lee, Sumi; Gil, Siye; et al. (Frontiers in Nutrition, 2024)
Weight-loss strategies through meal replacements are effective and sustainable options. However, few studies have assessed their effects on weight loss including body composition through proteinsupplemented meal replacements targeting the Asian population, including Koreans. This study aimed to assess the effectiveness and safety of a protein-supplemented very-low-calorie diet (PSVLCD) for weight reduction and changes in body composition in individuals with obesity over a 12-month long-term period. In total, 106 participants with obesity were randomly assigned to a PSVLCD or control group (food-based calorie-restricted diet). Body weight, waist circumference, body composition, and blood marker levels were measured throughout the study. Statistical analyses were performed to compare outcomes between the groups. Among the 106 participants, 84 completed the 12-month follow-up. Intention-to-treat analysis showed that the mean weight loss from baseline to 12 months was -6.86 kg (8.21% of baseline weight) in the PSVLCD group and -4.66 kg (5.47% of initial body weight) in the control group; the difference was -2.20 kg with a marginally significant interval (95% confidence interval [CI], -4.90; 0.50). Waist circumference (-8.35 cm vs. -4.85 cm; mean difference, -3.49 cm; 95% CI, -6.48 to -0.50) and visceral fat area (-28.28 cm 2 vs -13.26 cm 2 ; mean difference, -15.03cm 2 ; 95% CI, -29.01 to -1.04) also significantly decreased in the PSVLCD group at 12 months. In summary, in the PSVLCD group, a considerable initial reduction in waist circumference was sustained throughout the study period, with a marginally significant decrease in weight.